Therapeutic potential and mechanistic insights of silibinin targeting cancer-associated fibroblasts in colorectal cancer - He, Shenglan; Ji, Jianmei; Zhu, Kaisi; Chen, Youlan; Xu, Xiaowen (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to elucidate the role of SB in inhibiting CRC progression by targeting CAFs and elucidating the underlying mechanisms.MethodsIn this study, a spontaneous CRC model induced by AOM/DSS was used to evaluate the effects of SB on CAFs. Mice were treated with SB, and tumor burden was assessed by colon length. CAFs were isolated post-treatment for transcriptomic analysis to identify differentially expressed genes, with molecular docking providing in silico evidence of SB’s binding to target proteins. CAFs changes were further examined through HE staining, IHC, and assays for cell viability, colony formation, and migration. Integrated bioinformatic analysis elucidated the mechanistic role of SB in CAFs-mediated CRC progression.ResultsIn vivo studies showed that SB effectively reduced POSTN and α-SMA protein levels in CAFs in AOM/DSS-induced CRC mice. Consistently, in vitro experiments demonstrated that SB significantly decreased both protein and mRNA levels of α-SMA and POSTN in fibroblasts (colonic myofibroblast CCD-18Co cell lines.) co-cultured with CRC cell lines (human colorectal adenocarcinoma SW480 and RKO cell lines). SB also inhibited proliferation, colony formation, and migration of CCD-18Co cells. Transcriptomic and integrated bioinformatic analyses further suggested that SB exerts therapeutic effects on CAFs in CRC by modulating key target pathways.ConclusionThese results demonstrated that SB holds promise as a therapeutic agent for targeting CAFs in CRC. This study advances our understanding of SB’s mechanisms, particularly its inhibitory effects on CAFs proliferation, colony formation, and migration.